The Effect of Customer Loyalty and Location on Purchasing Decisions at Brastagi Supermarket Gatot Subroto - Agustiana, Intan Rizki; Sutantio, Andy; Felix, Felix; Nico, Nico; Pratama, Muhammad Farid; Rinaldi, Muammar; Khaira, Imamul (Outline Journal of Management and Accounting, 2024)
This study aims to determine the effect of Customer Loyalty and Location partially or simultaneously on Brastagi Supermarket Gatot Subroto. Population in this study are customers of Brastagi Supermarket for 50 customers. The sampling technique in this study used a saturated samples, which amounted to 50 customers. The research method used is the technique of collecting data through questionnaires. The analytical method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. T test results indicate that Customer Loyalty has no positive and insignificant effect on Purchase Decisions at Brastagi Supermarket Gatot Subroto and Location has a positive and significant effect on Purchase Decisions at Brastagi Supermarket Gatot Subroto. F test results indicate that Customer Loyalty and Location have a positive and significant effect on Purchase Decisions at Brastagi Supermarket Gatot Subroto. The coefficient of determination (R2) show that 35.3% of the Purchasing Decisions variable is influenced by the Customer Loyalty and Location variables, while the remaining 65.7% is influenced by other variables outside of this study such as service quality, store atmosphere, and promotion.